PENGARUH DIFERENSIASI PRODUK, DIVERSIFIKASI PRODUK, PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PT. KARYA ALAM SUKSES - Vannessa, Vannessa; Margery, Errie; Asmawiani Okta, Mila Asmawiani Okta (Fakultas Ilmu Sosial Dan Humaniora, Universitas Ibbi, 2025)
In an increasingly competitive business environment, product purchasing decisions are crucial to a company's success. In this moment, many companies are required to continuously innovate to remain competitive. With the growing number of product options available in the competitive market, consumer purchasing decisions become more complex. Therefore, companies need to develop strategies to meet consumers' needs and desires. The aim of this research is to identify and analyze the influence of Product Differentiation, Product Diversification, and Pricing on Consumer Purchase Decisions at PT. Karya Alam Sukses. The data collection techniques used in this research include questionnaires, documentation, and literature review. This research employs both qualitative and quantitative methods. The population in this research consists of consumers whose business licenses are in the form of a limited liability company (PT). The data used in this research are from the year 2023, involving 85 consumers. The sample consists of 85 consumers selected using a saturated sampling technique. The data analysis technique applied in this research is multiple regression analysis.The results of this research indicate that, partially, product differentiation has a positive but insignificant effect on purchasing decisions, product diversification has a negative but insignificant effect on purchasing decisions, and pricing has a positive but insignificant effect on purchasing decisions. However, simultaneously, product differentiation, product diversification, and pricing have a positive and significant effect on purchasing decisions.